The optimisation of fingermark enhancement by VMD and Lumicyano™ on thermal paper. Issue 2 (March 2020) - Sherriffs, Paul B.; Farrugia, Kevin J.; Fraser, Joanna M.; Jones, Benjamin J.
Highlights: Application of Lumicyano™ and of Au/Zn and Ag/Zn VMD on thermal paper. Different thermal papers required different amounts of gold and silver. Optimised Au/Zn and Ag/Zn varied in effectiveness on different thermal papers. Ag/Zn outperforms Au/Zn on fingermarks early in depletion series. Generally lower amounts of gold needed for enhancement than currently recommended. Abstract: The enhancement of fingermarks on thermal paper can be challenging due to background staining caused by polar solvents used in fingermark enhancement techniques such as ninhydrin. This study explored a commercial one-step superglue fuming process, Lumicyano™, and Vacuum Metal Deposition (VMD) to develop fingermarks on this substrate and overcome this issue. Different sequential treatments involving Lumicyano™ and a combination of VMD methods were investigated with varying degrees of success with some sequences being highly sensitive. The VMD processes, however, were observed to generally be more effective at enhancing marks, whereas Lumicyano™ provided little or no benefit on this paper type. The results indicate that Lumicyano™ is only beneficial as a pre-treatment when the entire sequence of gold/zinc and silver/zinc is taken to completion. The gold/zinc and silver/zinc VMD processes were optimised on five different thermal papers, and the optimised techniques were then directly compared to determine which was more successful on each thermal paper type as a single treatment.